2017
DOI: 10.20961/alchemy.v13i2.4890
|View full text |Cite
|
Sign up to set email alerts
|

APLIKASI METABOLOMIK BERBASIS HPLC UNTUK MENGIDENTIFIKASI WAKTU RETENSI KOMPONEN ANTIBAKTERI Stapylococcus aureus PADA EKSTRAK BUNGA KECOMBRANG (Etlingera elatior)

Abstract: ABSTRAKKecombrang (Etlingera elatior) dikenal sebagai tanaman herbal di Indonesia yang umumnya digunakan untuk obat tradisional dan pemberi aroma pada masakan daerah. Tujuan dari penelitian ini adalah untuk mengidentifikasi waktu retensi yang merupakan komponen antibakteri Stapylococcus aureus yang berasal dari ekstrak bunga kecombrang (Etlingera elatior) dengan menggunakan metode metabolomik berbasis HPLC. Aktivitas antibakteri dari ekstrak etanol, fraksi kloroform, dan fraksi air telah diuji dengan metode di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 8 publications
0
3
0
1
Order By: Relevance
“…According to Ghasemzadeh et al [3], Kelantan torch ginger flower extract at a concentration of 10 mg/mL gave 8.40 mm inhibitory power, while Johor torch ginger flower extract gave 4.00 mm inhibitory power, and Pahang torch flower ginger extract gave 9.20 mm inhibitory power. A previous report showed that the chloroform extract had an inhibitory value of 3.78 mm at a concentration of 500 mg/mL [7]. Differences in torch ginger flower source, extraction method, and solvent used can affect the concentration of secondary metabolites in the plants, consequently, influencing their antibacterial activity [3,19].…”
Section: Antibacterial Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…According to Ghasemzadeh et al [3], Kelantan torch ginger flower extract at a concentration of 10 mg/mL gave 8.40 mm inhibitory power, while Johor torch ginger flower extract gave 4.00 mm inhibitory power, and Pahang torch flower ginger extract gave 9.20 mm inhibitory power. A previous report showed that the chloroform extract had an inhibitory value of 3.78 mm at a concentration of 500 mg/mL [7]. Differences in torch ginger flower source, extraction method, and solvent used can affect the concentration of secondary metabolites in the plants, consequently, influencing their antibacterial activity [3,19].…”
Section: Antibacterial Activitymentioning
confidence: 99%
“…According to some previous research, torch ginger blossom has an antibacterial effect against S. aureus [3,6]. Testing the antibacterial activity of S. aureus on local torch ginger flower has been carried out by using the modification well diffusion method [7]. However, the identification of components of the antibacterial compound of S. aureus from local torch ginger flower has not yet been conducted.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Pada penelitian metabolomik, teknik pengujian menggunakan kromatografi cair kinerja tinggi (HPLC) yang dikombinasi dengan uji statistik multivariat digunakan untuk mengetahui profil metabolit seperti senyawa antibakteri dari ekstrak bunga kecombrang (Maser et al, 2017), komposisi senyawa fenol pada kulit citrus kering (Choi et al, 2011), komponen bioaktif daun torbangun (Yulianto et al, 2017), dan senyawa antioksidan dari rumput kebar (Aminudin et al, 2021). Demikian juga dengan penelitian-penelitian terhadap senyawa bioaktif jahe merah telah banyak diteliti, namun riset untuk mengetahui adanya korelasi antara aktivitas antioksidan dengan senyawa bioaktif dalam jahe merah menggunakan pendekatan metabolomik berbasis HPLC belum dilakukan.…”
Section: Alchemy Jurnal Penelitian Kimiaunclassified
“…Table 2 shows that kecombrang has been used as a medicine for cough, wound, eye, and fever, and to improve breast milk production, remove odor, and fertilize hair. Several studies have shown that kecombrang's flowers had antibacterial activity (Maser et al 2017;Ghasemzadeh et al 2015;Wijekoon et al 2013;Abdelwahab et al 2010;Lachumy et al 2010). Kecombrang contains bioactive compounds such as polyphenols, alkaloids, flavonoids, steroids, saponins and essential oils which are thought to have potential as antioxidants and also alternative natural preservatives (Wijekoon et al 2011).…”
Section: The Patterns Of Kecombrang Cultivation In Agroforestry Systemsmentioning
confidence: 99%